Of mitochondrion and COVID-19. (1st January 2021) - Alfarouk, Khalid Omer; Alhoufie, Sari T. S.; Hifny, Abdelhameed; Schwartz, Laurent; Alqahtani, Ali S.; Ahmed, Samrein B. M.; Alqahtani, Ali M.; Alqahtani, Saad S.; Muddathir, Abdel Khalig; Ali, Heyam; Bashir, Adil H. H.; Ibrahim, Muntaser E.; et al.
Abstract: COVID-19, a pandemic disease caused by a viral infection, is associated with a high mortality rate. Most of the signs and symptoms, e.g. cytokine storm, electrolytes imbalances, thromboembolism, etc., are related to mitochondrial dysfunction. Therefore, targeting mitochondrion will represent a more rational treatment of COVID-19. The current work outlines how COVID-19's signs and symptoms are related to the mitochondrion. Proper understanding of the underlying causes might enhance the opportunity to treat COVID-19.